Condition attendance of physical culture and other subjects of the Kharkiv students - Таможанська Ганна Валеріївна, (Ganna Tamozhanskaya); Пруднікова Марина Сергіївна, (Maryna Prudnikova) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to define reasons of admissions of employments on the physical culture of children and teenagers of general schools Kharkiv. Material and Methods: the analysis of school magazines of visit of lessons and medical maps is conducted 735 students (6–17 years) in 16 Kharkiv general schools, including. 462 boys, 273 girls; analysis of health and sporting sections in these general schools and their visited from the incurrence of students. Results: the features of visited of employments on physical culture and other general theoretic articles of students of junior, middle and senior classes are Set. The amount of students is determined visitant different sporting sections in extracurricular time. Conclusions: the visited of students is certain basic, preparatory and special medical groups of employments on physical culture and other general theoretic objects.